Research progress of T lymphocytes associated with recurrent spontaneous abortion - LIANG Dingyu; YANG Yihua (Guangxi Yike Daxue xuebao)
Recurrent spontaneous abortion (RSA) is a pregnancy complication with a complex etiology that seriously affects the physical and mental health of women of reproductive age. Although RSA is commonly thought to be caused by an imbalance in maternal-fetal immune tolerance, its specific immune mechanisms are not yet fully understood. Recent studies have found that an imbalance in the immune microenvironment at the maternal-fetal interface, particularly abnormalities in the function and number of T lymphocytes and their related subsets, are closely related to the occurrence of RSA. This paper aims to review the latest research progress on T lymphocyte changes in RSA, exploring the potential connections between immune cell imbalance in the maternal-fetal interface immune microenvironment and RSA, so as to provide references for basic research and clinical treatment strategies.